Liver stiffness change with HCV cure in HIV-infected patients on non-nucleoside analogues. (22nd May 2021) - Gonzalez-Serna, A.; Corma-Gomez, A.; Tellez, F.; García-Martin, S.; Rivero-Juarez, A.; Frias, M.; Vera-Méndez, F. J.; De los Santos, I.; Merino, D.; Morano, L.; Imaz, A.; Galera, C.; et al.
Abstract: Background: Liver stiffness (LS) at sustained viral response (SVR) is strongly associated with a lower incidence of subsequent hepatic events. HIV NNRTIs may have a beneficial impact on fibrogenesis. Objectives: Our aim was to analyse the influence of NNRTI-based therapy on the change in LS from starting direct-acting antiviral (DAA) therapy to achieving SVR in HIV/HCV-coinfected patients. Methods: Three hundred and thirteen HIV/HCV-coinfected patients who fulfilled the following criteria were included: (i) had achieved SVR with an IFN-free, DAA-including regimen; (ii) LS ≥9.5 kPa before therapy; (iii) LS measurement available at SVR; (iv) seronegative for HBsAg; and (v) ART containing 2 NRTIs plus either 1 NNRTI or 1 integrase inhibitor (INI) or 1–2 NRTIs plus 1 PI. LS changes were assessed. Results: Seventy-four patients received NNRTI-based combinations [53 (71.6%) rilpivirine and 16 (21.6%) efavirenz] and 239 patients received other regimens. At baseline, the median (IQR) LS was 16.7 kPa (11.8–25.6) in the NNRTI group and 17.3 kPa (11.9–27.4) in the non-NNRTI group ( P  =   0.278). The median (IQR) percentage of LS decrease from baseline to SVR was 35.2% (18.2%–52.3%) for NNRTI-based therapy and 29.5% (10%–45.9%) for PI- or INI-based therapy ( P  =   0.018). In multivariate analysis, adjusted for sex, age, HCV genotype, NRTI backbone and propensity score for HIV therapy, NNRTI-based regimen use was associated with a higher LS decrease [β = 11.088 (95% CI = 1.67–20.51); P  =   0.021]. Conclusions: Treatment with NNRTI plus 2 NRTI combinations is associated with a higher LS decline than other ART combinations in HIV/HCV-coinfected patients receiving DAA-based therapy.